CARACTERUL PROSPECTIV AL EDUCAŢIEI: ABORDARE DIN PERSPECTIVĂ ISTORICĂ - USM ADMIN (Moldova State University, 2010)
It is undisputed that the educational system through its aspects preparing the personality and guiding her to the future. Focusing on the character education has been shown prospectively since antiquity, although it was not a direct focus, the literature proves this. So we decided to approach prospective nature of education in historical perspective, highlighting the epoch to epoch, the increasing focus of the prospective nature of education.